Analisis Tindak Tutur Kata dan Ragam Bahasa Dalam Komunikasi Komunitas LGBT - Agnes Monica Sianipar; Brigita Zai; Enjel Widia Sari Gea; Mutia Annisa; Nakita Nakita; Respa Mellia Sirait (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
The purpose of this study is to find out how language, actions, and speech are used in the LGBT community, especially lesbians. This study uses descriptive qualitative methodology. The data used are primary data and secondary data. Primary data was obtained directly from informants through interviews, gestures, or behaviors related to the research variables. Secondary data comes from documents, notes, photos, recordings, or tables that support primary data. The results of this study allow us to conclude that assertive and expressive speech dominated the answers of this interview. The interviewees provided a lot of information, opinions, and their own experiences about language use in the LGBT community..